Palmares revisitado - Thornton, John K. (Afro-Ásia, 2022)
Resenha de: LARA, Silvia Hunold. Palmares & Cucaú: o aprendizado da dominação. São Paulo: EdUSP, 2021. 451 p. LARA, Silvia Hunold; e Fachin, Phablo Roberto Marchis (orgs.). Guerra contra Palmares: o manuscrito de 1678. São Paulo: Chão Editora, 2021. 230 p.